Antibiotic resistance evolution of methicillin resistant Staphylococcus aureus (MRSA) and colloidal silver as the nanoweapon - New, Chia Yeung; A. R., Amalia; Bahumaish, Ramzi Othman Saeed; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
As the society begin to realize the importance of combating antimicrobial resistance, going back to silver might be the solution. Silver has been known for its potential antimicrobial activity since ancient times and, the development of nanoparticles has increased its potential into becoming an antimicrobial agent that can be applied in broad-spectrum. Antimicrobial resistance has spread into an irrepressible manner which requires drastic action plan as a number of pathogenic bacteria began to acquire resistance genes. Methicillin Resistant Staphylococcus aureus (MRSA) is one of the earliest reported resistant clones which is the center of this study. This study focused on the dissemination and evolution of MRSA on its resistance towards antibiotics. Disc Diffusion Test was employed to create the antibiograms of MRSA isolates. All isolates showed resistance towards amoxicillin, ampicillin, cefazolin, oxacillin and penicillin. In contrast, all isolates were susceptible towards erythromycin. The findings also discovered isolates that were vancomycin-resistant (66.7%) and vancomycin-intermediate (33.3%). As the efficacy of antibiotic treatment is at a question, we also investigated on the antimicrobial activity of colloidal silver in the hope as an alternative treatment. Shiga Toxin producing Escherichia coli (STEC) and MRSA (ATCC 33591) was tested using modified Quantitative suspension test for the evaluation of bactericidal activity for chemical disinfectants and antiseptics based on BS EN 1276:2009. The outcome of this study indicated that the colloidal silver is working effectively against STEC and MRSA (ATCC 33591), showing killing percentages well above 99.0% at 4 minutes and 8 minutes of contact. Vancomycin-resistant S. aureus (VRSA) and Vancomycin-intermediate S. aureus (VISA) were also tested and the results indicated that VISA had higher killing percentages at 4 minutes (99.83%) and 8 minutes (99.85%) compared to VRSA at 4 minutes (96.72%) and 8 minutes (98.35%). This opens a solution to the rising problem of antimicrobial resistance.